Organizational Governance for the 21st Century: Arriving at a Global View. Issue 162 (19th March 2019) - Hurth, Victoria; Kravatzky, Axel
Abstract : The world needs excellent standards of organizational governance. Here Dr. Victoria Hurth and Dr. Axel Kravatzky, conveners of the first global standard in governance of organizations (ISO 37000), discuss why the time is right for asking the world what it thinks good governance means and how it can be achieved.